Da teoria à práxis: a importância da sequência didática na formação de professores de geografia - Soares, Eliane Scandelai (2015)
This study aims to articulate the development of intelligence theories with geography learning with respect to textual production of the students. The research is based on the importance of contributing to the formation of autonomous teachers, able to promote a holistic geography teaching in view of all for parties, ie, the complex knowledge to the simple. The dissertation was developed from the development and implementation of didactic sequences that enable the construction of knowledge from the perspective of the relationship between subject - subject, in contrast, the subject-object relationship. This methodology points to the possibility of making the classroom, a truly space dedicated to the production of geographical knowledge and development of cognitive abilities from the rational faculty pedagogical intervention. The production of knowledge within this complexity is through the development of oral and written language that, from the recovery and reconstruction of geographical concepts, can dialogically, establish specific cognitive links between students' prior knowledge and the knowledge to be produced and worked in the school environment. Therefore, we will at first the contribution of theories (PIAGET, 2009, VYGOTSKY, 2007 and BAKHTIN, 2011) for the teaching of geography. Then, we discuss the relationship between geography and education (STRAFORINI, 2001) historically situating the changes in teaching geography (MOREIRA, 2008; LACOSTE, 2008), reflecting on the dilemmas in educational practice and teacher training. Finally, we will stop the application of the analysis of the methodology of teaching sequence by discursive genres (SCHNEUWLY, NOVERRAZ and DOLZ, 2007). The results of this survey reflect on a new direction in the construction of geography teaching in the classroom, related to the social body and the production of language in day-to-day students present in basic education, making them subject participatory reflection of historical process and construction of space which is its own existence